Cecropiaceae endémicas del Perú - Cáceres, Pamela (2006)
The Cecropiaceae are represented in Peru by three genera and 58 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004; Berg & Franco, 2005), all of them trees or hemiepiphytes. Here we recognize six endemic species in two genera. Endemic Cecropiaceae are found in the Humid Lowland Amazonian Forests and Very Humid Montane Forests regions, between 500 and 2000 m elevation. We applied IUCN categories and criteria to five species. Two Cecropiaceae species have been recorded from Peru´s protected areas system.